2013
DOI: 10.1021/es404156a
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Gas Phase Nitrous Acid onto Boundary Layer Soil Surfaces

Abstract: Nitrous acid (HONO) is an important OH radical source that is formed on both ground and aerosol surfaces in the well-mixed boundary layer. Large uncertainties remain in quantifying HONO sinks and determining the mechanism of HONO uptake onto surfaces. We report here the first laboratory determination of HONO uptake coefficients onto actual soil under atmospheric conditions using a coated-wall flow tube coupled to a highly sensitive chemical ionization mass spectrometer (CIMS). Uptake coefficients for HONO decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 74 publications
6
74
0
Order By: Relevance
“…Either process increases with relative humidity, which is a possible explanation for the decrease in NO 2 À (p) /HONO (g) during the warm and dry period after 11 June during the campaign. More recently, Donaldson et al [2014] have demonstrated by flow tube experiments that soil layers will take up HONO (g) efficiently under atmospheric conditions, consistent with the previous findings of VandenBoer et al [2013] during NACHTT-11, leaving nitrite at the surface. The authors suggest uptake by an adsorption mechanism, but HONO (g) was not released back to the gas phase after exposure, indicating an irreversible sink that may also be reactive in nature.…”
Section: 1002/2013jd020971supporting
confidence: 89%
See 2 more Smart Citations
“…Either process increases with relative humidity, which is a possible explanation for the decrease in NO 2 À (p) /HONO (g) during the warm and dry period after 11 June during the campaign. More recently, Donaldson et al [2014] have demonstrated by flow tube experiments that soil layers will take up HONO (g) efficiently under atmospheric conditions, consistent with the previous findings of VandenBoer et al [2013] during NACHTT-11, leaving nitrite at the surface. The authors suggest uptake by an adsorption mechanism, but HONO (g) was not released back to the gas phase after exposure, indicating an irreversible sink that may also be reactive in nature.…”
Section: 1002/2013jd020971supporting
confidence: 89%
“…The typical diurnal cycle shown in Figure 3 can be explained by photolysis during the day (R1) and accumulation overnight, most likely from heterogeneous conversion of NO 2 on wet surfaces (R3) with increasing relative humidity over the course of a night. [Czader et al, 2012;Wong et al, 2011], but the fate of HONO (g) lost to the surface is uncertain, despite new constraints on surface uptake showing consistency with those derived by models [Donaldson et al, 2014;VandenBoer et al, 2013]. Figure 4 shows that the absolute mass loading of NO 2 À (p) generally scales according to the measured amount of HONO (g) .…”
Section: Intercomparison Of Hono (G) Measurements Between Aim-ic and mentioning
confidence: 76%
See 1 more Smart Citation
“…Maljanen et al (2013) measured a maximum HONO flux of about 2 µg m −2 h −1 in terms of N. This would equal a source strength of 7.1 × 10 3 molecules cm −3 s −1 (1 ppt h −1 ) considering a boundary layer height of 1000 m and hence is negligible. The laboratory measurements of soil samples represent potential HONO emission fluxes as HONO can simultaneously be taken up by soil (Donaldson et al, 2014) or deposited to soil and re-emitted as proposed by VandenBoer et al (2013). In addition to emissions from the soil surface, the evaporation of dew can release HONO (He et al, 2006), also enhancing HONO fluxes in the early morning when temperatures increase.…”
Section: Indirect Influence Of J (No 2 ) On P Unknownmentioning
confidence: 99%
“…Nocturnal HONO formation is partly counteracted by HONO uptake on the ground, with reported surface uptake coefficients in the range of 2×10 −5 to 2×10 −4 (VandenBoer et al, 2013;Donaldson et al, 2014;Wong et al, 2012). Uptake on aerosol is also likely, but little information on this process is available.…”
Section: Introductionmentioning
confidence: 99%